Conversation analysis: psychotherapist interventions in different gender university students with depressive conditions and suicidal ideation - Lautaro Barriga; Marco Villalta; Camila Navarrete; Diego Benavides (Journal of Men's Health, 2022)
Background: Research shows that university students have increased prevalence of depressive disorders with suicidal ideation. The aim of the study is to analyze the psychotherapist’s interventions in university students with a diagnosis of mild depression and suicidal ideation attended in a psychological center of an accredited university. Methods: Descriptive study of multiple cases and mixed method. The sessions were divided into three time segments to recognize the interventions used by the psychotherapist in the four therapeutic dyads. Results: Although the students share the same diagnosis, the psychotherapist’s interventions are different according to the gender and experience of the psychotherapist. The greater the experience, the more binding and chain interventions are used, while the psychotherapist in training uses expansion, change and explanatory interventions. Conclusions: Interventions are distributed differently throughout the sessions, are engaged according to the years of experience of the psychotherapist and the gender of the student. The diagnosis of depression does not affect the type of intervention used.